Histomorphometric study of cortical bone in edentulous ridges and its relationship with cone beam computed tomography. Preliminary results - Garcia Linares, Sixto Angel (2020)
Objective. Determine the relationship of bone quality in cortical bone according to the different regions of the maxilla and mandible by histomorphometry and the equivalent Hounsfield values of Cone Beam computed tomography in partially edentulous patients. Methods. This cross-sectional study analyzed histomorphometry according to the number of osteons, osteocytes and thickness of the cortical bone and the Hounsfield units in the Cone Beam computed tomography according to gender and regions of the maxilla and mandible to determine the existing correlation in 29 patients from Graduate Clinic of The Faculty of Dentistry at the National University of San Marcos. Results. Hounsfield units average was 593 ± 121.10 in the male gender and 570 ± 127.35 in the female gender. number of osteons average was 16.5 ± 2.71 male and 12 ± 4.68 in the female. Number of osteocytes average was 179 ± 39.99 male and 124 ± 50.55 in the female. About cortical alveolar bone thickness in males, it was 33 ± 50.55 microns and 31 ± 8.91 in females. It was found normal distribution between the data. Pearson's correlation between Hounsfield units and quantitative variables cortical thickness, number of osteons, and number of osteocytes. Conclusion. There is a statistically significant moderate positive correlation between the thickness of the cortical bone and the Hounsfield units (r=0.452, p<0.01).